Uwarunkowania wydolności funkcjonalnej chorych z dyskopatią lędźwiowo-krzyżową poddanych leczeniu zachowawczemu - Snarska, Katarzyna Krystyna; Małyszko, Jolanta; Charyton, Monika; Bachórzewska-Gajewska, Hanna; Drozdowski, Wiesław (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2015)
Introduction. Back pain has now become a disease of our civilization. One of the reasons being the herniated nucleus pulposus, which often leads to a restriction in various aspects of the bio-psycho-physical functioning. These disorders intensify the pain discomfort which occurs. Aim. Assessment of functional capacity in the case of patients with lumbar discectomy-cross treated conservatively and the evaluation of the lumbosacral disc disease impact on the quality of life. Material and Methods. The study included 181 patients, two days before discharge from hospital, hospitalized in the Department of Neurological Clinic, at the Medical University of Bialystok in the period from June to December 2013 due to lumbosacral disc disease. The research tools included: our questionnaire, the WHOQOL-BREF Scale assessing the quality of life, as well as the Visual Analogue Scale — VAS. Results. The group of respondents included 102 women (56.4%) and 79 men (43.6%) aged 24–76 years (mean age 48.3±12.7 years). The overall quality of life for the studied group of patients with lumbosacral discopathy ranged at the level of 3.32±0.83, which indicates patients’ average satisfaction with their quality of life. Self-assessment of health condition on scale from 1 to 5 ranged 2.83±0.99, which meant average satisfaction with health condition. The respondents working mentally better assess the physical realm, while those with higher education better evaluated the quality of their lives. Lonely people worse assessed the psychological sphere than those married or not-married. Feeling the pain discomfort of strong and maximum intensity significantly affected patients’ assessment regarding the physical sphere and resulted in the decrease of the quality of life. Conclusions. 1. There is a relationship between the functional capacity of patients with lumbosacral discopathy and the type of work performed, marital status, the level of education, and risk factors. 2. Patients with lumbosacral discopathy of the spine, especially those feeling strong pain, have a reduced quality of life, particularly in the field of physical fitness. (JNNN 2015;4(1):4–12)